EFFECT OF TREE AGE ON WOOD PROPERTIES OF EUCALYPTUS CAMALDULENSIS IN THAILAND - Pisuttipiched, Sawitreee (วารสารวนศาสตร์ไทย, 2022)
The main objective of this study was to study the effect of tree age on basic density. chemical composition, and the fiber morphology of wood. The materials used in this study were 4, 6 and 8 years old Eucalyptus camaldulensis plantation trees from the same clone. The plantations located at the eastern part of Thailand and were not far from each other. All experiments were performed in laboratory scale. Three debarked wood disks from each tree age were cut at 1.3 m above ground for analyzing wood density, chemical composition, fiber length and coarseness, cell distribution and fiber wall thickness. The wood density of E. camaldulensis increased with increasing tree age: density level was high, 550 to 650 kg/m3. Pentosan content decreased slightly while pitch content increased with age. There was a lot of tylose deposited inside the vessels of the 4th growth ring of 8 year old trees. Older trees had longer and coarser fibres, but the effect seemed to be leveled off at the age of 6 years. In general, fibre coarseness was very low. Vessel and fiber volumes increased from pith to bark, especially at the 6- to 8-growth rings of 8 years old trees. Tree age did not affect fiber diameter but wall thickness slightly increased while lumen decreased with increasing tree age.